Utilization Factors of HIV Testing by Pregnant Women in Primary Health Care - Hasibuan, Rapotan (LPPM Universitas Prima Nusantara Bukittinggi, 2024)
Background: Utilization of HIV testing during pregnancy is one of the policy efforts to prevent pregnant women from contracting the HIV virus or transmitting it to the unborn fetus. Deli Serdang has always been in second place in the district with the most HIV cases over the last 3 (three) years in North Sumatra. On the other hand, HIV testing by pregnant women in this district is relatively low, with a number of factors assumed to be the cause.Objective: This study aimed to investigate several factors with the use of HIV testing by pregnant women so that strategic efforts can be obtained to prevent HIV transmission by pregnant women.Methods: This research adopts a quantitative approach and employs a cross- sectional study design. The data collection period spans from June to July 2023, and the study was conducted within the operating area of in 5 (five) Primary healthcare areas with the most HIV cases in Deli Serdang regency. The sample was obtained using a cluster random sampling technique so that 285 pregnant women were obtained. Data were collected using a questionnaire that had been tested for validation and reliability, and then analyzed univariately, bivariately using the Chi-Square test, and multivariately using Binomial logistic regression.Results: This study found a significant relationship between the variables of knowledge, social support, facilities and infrastructure, and the perspective of vulnerability with the use of HIV testing, respectively. Conclusion: The conclusion of this study found that there was a relationship between the utilization of HIV testing by pregnant women in the work area of the Puskesmas with knowledge, attitudes, facilities and infrastructure as well as a vulnerability perspective. Strategic and tactical efforts in the form of appropriate interventions in the provision of supporting facilities and infrastructure desired by pregnant women will enable an increase in HIV testing.